Pengembangan Media Pembelajaran Video Animasi Powtoon pada Materi Telur - Nia Rachmawati; Nugrahani Astuti; Mauren Gita Miranti; Ita Fatkhur Romadhoni (Pusat Riset dan Inovasi Nasional, 2023)
This research is development research that aims to find out: 1) the development of powtoon animation video learning media on egg material; 2) the feasibility of powtoon animation video learning media on egg material; and 2) students' responses to the powtoon animation video learning media on egg material. This study uses the 4D development method, but only up to the development stage. Data were obtained using validation sheets and questionnaires using a Likert scale. The validation sheet was assessed by an expert judgment which was tested with the Aiken V formula. The questionnaire sheet was assessed by students who then carried out a practicality test to see students' responses to learning media. Based on the results of the data analysis performed, the material validation results obtained an Aiken V value of 0.959. The media validation results obtained an Aiken V value of 0.954. Meanwhile, from the results of the student response questionnaire, they obtained a percentage value of 80.6% in the very practical category. This shows that the powtoon animation video learning media on egg material is feasible, very practical, and can be used in DDPK 2 learning egg material.